Comparison of Three Formulations of Alphachloralose For Immobilization of Canada Geese - Belant, Jerrold L.; Seamans, Thomas W. (DigitalCommons@University of Nebraska - Lincoln, 1997)
The effectiveness of an alpha-chloralose (AC)-corn oil suspension, an AC-margarine mixture, and AC tablets were compared for immobilizing Canada geese (Branta canadensis). Responses to AC immobilization also were compared in male and female Canada geese. There was no difference in mean time to first effects or mean time to capture between male and female geese dosed with 30 mg/kg AC in orally-administered bread baits. Recovery times (≤24 hr) also were similar between sexes. Mean (±SE) time to first effects for geese immobilized with AC tablets in bread baits ( 19 ± 3 mm) was significantly less than mean time to first effects for geese immobilized with AC in margarine (28 ± 6 mm) or AC in corn oil (32 ± 7 mm) applied to bread baits (n = 12 geese/treatment). Respective mean times to capture geese immobilized with AC tablets, AC-margarine, and AC-corn oil were not significantly different at 62 ± 25, 89 ± 48, and 88 ± 30 mm, respectively. Ten, 11 and, seven geese immobilized with AC tablets, AC-margarine, and AC-corn oil recovered within 24 hr, respectively; all geese recovered within 28 hr. Male and female Canada geese respond similarly to AC immobilization, at least during molt, and AC mixed with margarine or AC in tablet form is at least as effective as the presently used AC-corn oil suspension. AC tablets or AC-margarine also would be more practical for some field situations. Additional development of AC tablets will be required prior to field use for capturing nuisance waterfowl.